Analysis of Athletes Physical Conditions During the Covid 19 Pandemic - Santika, I Gusti Putu Ngurah Adi (Universitas Negeri Semarang, 2021)
The Covid 19 pandemic has hit the world. Athletes are athletes who strive to provide maximum performance. With the current pandemic situation, problems arise regarding the physical condition of athletes, especially athletes from the PGRI Mahadewa University Indonesia. Students who work as athletes do not know the extent of their physical condition during the Covid 19 pandemic. The purpose of this study was to determine the physical condition of athletes during the Covid 19 pandemic. The research sample was 30 male athletes from the University of PGRI Mahadewa Indonesia. Based on the physical condition examination, the results showed that the average physical condition of the athletes which consisted of cardiovascular endurance was 34 ml/kg/mt (less), right hand muscle strength was 46.7 kg (good), left hand muscle strength was 38.7 kg (moderate), the tensile strength of the shoulder muscles is 15.7 kg (very less), the thrust of the shoulder muscles is 26.0 kg (moderate), the strength of the back muscles is 60.3 kg (less), the strength of the leg muscles is 154.6 kg (moderate), explosive power leg muscles 48 cm (less), arm muscle endurance 53 x/minute (moderate), body balance 38 seconds (good), body speed 4.80 seconds (less), reaction speed to light stimulus 1.394 seconds (less), reaction speed sound stimulus 1.193 seconds (less), body agility 15.02 seconds (less), body flexibility 20.60 cm (very little), and body fat content of 21% (slightly high). Based on these results, of the 15 components outside of body fat levels, 2 physical components are at a very low level, 7 physical components are at a low level, 4 components are at a moderate level, and 2 physical components are at a good level.